The National Export Strategy 2010-2014, a realistic alternative for the attenuation of the crisis effects - LIANU, Costin (Annals of Spiru Haret University. Economic Series, 2010)
The Romanian economy is passing an economic recession period induced both by the persistence of the global financial crisis and the alarming evolution of the budget deficit and the consequences of the austerity measures upon the economic environment. In the actual conditions, Romania’s external creditors ascertain and impose certain limits for the budget expenses, necessary for a financially stable economy. The imposed limitation or self-limitation of the expenses for a 6 months sacrifice period, that could reach one year or longer, does not guarantee the economic re-bounce when the measurements for the strategic attenuation of the crisis, for the creation of a sustainable and competitive economy, are inexistent. Certain long term strategic aspects to which the external creditors, especially the IMF do not pay enough attention, but that can assure the sustainability and competitiveness belong to the internal component of the business environment and climate, to the ways to fight corruption, bureaucracy, tax evasion or they assure legislative predictability in order to support a transparent and competitive environment and the development of a new managerial culture. Others belong to the manner in which we will manage to assure national solidarity through justice, social or medical assistance or the influence of the politic aspect on the economy, on the administration in the other spheres of the social and economic life. These depend mostly on how the political sphere will manage to reform itself. Others belong to the educational reformation and the growth of the educational services suppliers’ capacity or to the research to sustain the companies’ competitiveness.